Initiation of the Wrangell arc: a record of tectonic changes in an arc-transform junction revealed by new geochemistry and geochronology of the ~29–18 Ma Sonya Creek volcanic field, Alaska - Berkelhammer, Samuel Ethan (Kansas State University, 2017)
The Sonya Creek volcanic field (SCVF) contains the oldest in situ magmatic products in the ~29 Ma–modern Wrangell arc (WA) in south-central Alaska. The WA is located within a transition zone between Aleutian subduction to the west and dextral strike-slip tectonics along the Queen Charlotte-Fairweather and Denali-Duke River fault systems to the east. WA magmatism is due to the shallow subduction (11–16°) of the Yakutat microplate. New ⁴⁰Ar/³⁹Ar and U-Pb geochronology of bedrock and modern river sediments shows that SCVF magmatism occurred from ~29–18 Ma. Volcanic units are divided based on field mapping, physical characteristics, geochronology, and new major and trace element geochemistry. A dacite dome yields a ~29 Ma ⁴⁰Ar/³⁹Ar age and was followed by eruptions of basaltic-andesite to dacite lavas and domes (~28–23 Ma Rocker Creek lavas and domes) that record hydrous, subduction-related, calc-alkaline magmatism with an apparent adakite-like component. This was followed by a westward shift to continued subduction-related magmatism without the adakite-like component (e.g., mantle wedge melting), represented by ~23–21 Ma basaltic-andesite to dacite domes and associated diorites (“intermediate domes”). These eruptions were followed by a westward shift in volcanism to anhydrous, transitional, basaltic-andesite to rhyolite lavas of the ~23–18 Ma Sonya Creek shield volcano (Cabin Creek lavas), including a rhyolite ignimbrite unit (~19 Ma Flat Top tuff), recording the influence of local intra-arc extension. The end of SCVF activity was marked by a southward shift in volcanism back to hydrous calc-alkaline lavas at ~22–19 Ma (Young Creek rocks and Border Lavas). SCVF geochemical types are very similar to those from the <5 WA, and no alkaline lavas that characterize the ~18–10 Ma Yukon WA are present. Sr-Nd-Pb-Hf radiogenic isotope data suggest the SCVF data were generated by contamination of a depleted mantle wedge by ~0.2–4% subducted terrigenous sediment, agreeing with geologic evidence from many places along the southern Alaskan margin. Our combined dataset reveals geochemical and spatial transitions through the lifetime of the SCVF, which record changing tectonic processes during the early evolution of the WA. The earliest SCVF phases suggest the initiation of Yakutat microplate subduction. Early SCVF igneous rocks are also chemically similar to hypabyssal intrusive rocks of similar ages that crop out to the west; together these ~29–20 Ma rocks imply that WA initiation occurred over a <100 km belt, ~50–60 km inboard from the modern WA and current loci of arc magmatism that extends from Mt. Drum to Mt. Churchill.
Keywords: Igneous petrology; Wrangell arc; Sonya Creek volcanic field; Alaskan volcanism; Tectonics; Radiogenic isotopes